The THE INFLUENCE OF EDUCATIONAL BACKGROUND ON THE KNOWLEDGE OF DRUG USES DURING FASTING IN SAMARINDA - Deasy Nur Chairin Hanifa (Universitas Muhammadiyah Kalimantan Timur, 2019)
At the time of fasting proper use of drugs is needed, because the schedule of taking different drugs will affect of the drug. Schedule for taking medication affects the fate of drugs in the body, because it needs to be careful in changing the schedule of taking medication. So it can be said that the need for knowledge of drug use during fasting. The aim of this study was found the influence of educational background, especially in the health and non-health fields on knowledge of drug use during fasting. This research was conducted by survey testing using Google Form, by submitting several statements regarding the knowledge of drug use during fasting which is listed in the KDUF (Knowledge of Drug Use during Fasting) questionnaire. The total value of the questionnaire is categorized into 3, namely low, moderate, and good. The results showed that the moderate knowledge category in the health group is 26% and non-health is 30%, while the knowledge category is good for the health group at 74% and the non-health group at 70%. The results of the statistical analysis showed no significant relationship between the background of health and non-health education (P> 0.05). So it can be concluded that there is no difference in the influence of health and non-health education background on knowledge of drug use during fasting.